A Comprehensive Study on Addressing Trust Erosion in Multimedia in The Indian Context - Manu, Kshema; S, Malathi (The Scientific Temper, 2025)
The widespread use of multimedia helps users to connect, create, and inform easily, but the consequences of inappropriate usage, including altered content, deepfakes, and misleading material, are severely damaging. It can undermine trust, influence public opinion, deceive people, go against Government rules and regulations, and even incite violence due to its inherent characteristic of being quick and widespread. Spreading illicit material, committing cyberbullying, and harassing individuals are a few cases of multimedia misuse. An integrated approach combining technology, digital literacy, critical thinking, guidelines, and timely legal reforms is the only possible solution to curb the complexity of multimedia misuse. The observations made in this paper advocate for stronger legislative measures and cross-disciplinary collaboration to address the evolving landscape of trust erosion.